(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
School snack safety is a crucial component of public health protection, particularly for elementary-level learners who are vulnerable to food contamination and exposure to harmful chemical substances. This community service activity aimed to enhance participants’ understanding and awareness of safe snack consumption through a Chemical Communication, Information, and Education (CIE) approach. The program was conducted at Public Elementary School 104242 Lubuk Pakam and consisted of interactive learning sessions, visual demonstrations, simple explanations of chemicals, and guided discussions on hazardous food additives, artificial colorants, preservatives, and common indicators of unsafe snacks. The educational materials were designed to ensure that participants could easily comprehend the chemical risks associated with unsafe foods sold in their surroundings. Assessments were conducted to evaluate changes in knowledge and attitudes. The results showed a significant improvement in participants’ ability to identify unsafe snacks, recognize basic chemical hazards, and make safer decisions when selecting food. This program underscores the importance of incorporating chemical literacy into school-based health promotion initiatives. Strengthening participants’ understanding of chemical safety contributes to better food choices and supports the creation of a healthier and safer school environment.